Pre-service Teachers’ Decision-Making and Classroom Assessment Practices - Oo, Cherry Zin; Alonzo, Dennis; Davison, Chris (Frontiers in Education, 2021)
Classroom assessment practices play a pivotal role in ensuring effective learning and teaching. One of the most desired attributes of teachers is the ability to gather and analyse assessment data to make trustworthy decisions leading to supporting student learning. However, this ability is often underdeveloped due to insufficient attention to authentic assessment practices in most teacher education curricula. There is a need to ensure that teacher education focuses on assessment for learning (AfL), demonstrating how to integrate assessment into teaching that teachers can make trustworthy decision to develop student learning. In addition, teachers report feeling overwhelmed by the complex process of data analysis and decision-making. This paper reports on the results of a study of the process of pre-service teachers’ (PSTs) decision-making in assessment practices with real students and in real classroom conditions through the lens of teacher agency. Using a design-based research methodology, a needs-based professional development program for PSTs’ assessment literacy was developed and delivered. Following the program, thirty PSTs in the intervention group were encouraged to implement the assessment strategies during their practicum. Semi-structured individual interviews were undertaken with the intervention group before and after their practicum in schools. This data was analysed together with data collected during their practicum, including lesson plans, observation checklists and audiotapes of lessons. The analysis shows that PSTs’ decision-making in the classroom was largely influenced by their beliefs of and values in using assessment strategies but, importantly, constrained by their supervising teachers. The PSTs who understood the principles of how AfL and wanted to implement on-going assessment and use the results to make decisions about learning and teaching activities experienced tension with supervising teachers who wanted to retain high control of the practicum. Those PSTs who were allowed greater autonomy during their practicum and understood AfL assessment strategies had greater freedom to experiment, which allowed them multiple opportunities to apply the result of any assessment activity to improve both their own teaching and students’ learning. The paper concludes with a discussion of the kind of support PSTs need to develop their assessment decision-making knowledge and skills during their practicum.